2011
DOI: 10.1002/ijc.26025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intracellular alpha fetoprotein on retinoic acid receptors‐mediated expression of GADD153 in human hepatoma cell lines

Abstract: The aim of our study was to gain a better understanding of the molecular mechanism underlying the previously unrecognized role of cytoplasmic alpha fetoprotein (AFP) in retinoic acid receptors (RAR) mediated expression and biological effects of GADD153. Using microarray analysis, the expression of the GADD153 gene showed the greatest fold change among apoptosis/growth related genes in response to ATRA. AFP was able to interact with RAR in HepG2 cells, which was undetectable in HLE cells owing to absence of AFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Afp may function as a signal molecule by binding with nuclear receptors including retinoic acid receptors, transcription factors, and other proteins (28,29). Thus, the high levels observed in our implantation sites might be interfering with the retinoic acid action in fetal tissues.…”
Section: Discussionmentioning
confidence: 94%
“…Afp may function as a signal molecule by binding with nuclear receptors including retinoic acid receptors, transcription factors, and other proteins (28,29). Thus, the high levels observed in our implantation sites might be interfering with the retinoic acid action in fetal tissues.…”
Section: Discussionmentioning
confidence: 94%
“…Once released from the late endosomal vesicle, the receptor is separated and recycled back to the cell membrane or degraded. AFP can either be stored in the perinuclear spaces or be engaged in activating or inhibiting signal transduction pathways in the cytoplasm …”
Section: Discussionmentioning
confidence: 99%
“…Given that AFP may interact with RAR and interfere with RAR signaling, AFP might therefore interfer with function of genes regulated by ATRA/RAR . Included among the apoptosis/growth related genes regulated by ATRA/RAR which stimulated our interest is Growth arrest and DNA damage 45α ( GADD45α ), which is upregulated up to 9.5‐fold after ATRA administration . Moreover, as tumor suppressor gene GADD45α has a potential RAR recognition site in the upstream region, and was therefore chosen as a target gene for further evaluation of the effect of AFP on the RAR signal pathway.…”
mentioning
confidence: 99%
“…In our previous research, intracellular AFP was shown to be a signal molecule. Recently, a number of proteins, including nuclear receptors and other intracellular signal molecules involved in cell growth or apoptosis, have been reported to bind to cytoplasmic AFP [4, 5, 7, 30]. These results indicated that the poor prognosis associated with high APF is caused by high cell proliferation, high angiogenesis and low apoptosis.…”
Section: Discussionmentioning
confidence: 99%